ANALISIS BAKTERI Escherichia coli PADA BUDIDAYA IKAN NILA (Oreochromis niloticus) DI TAMBAK-TAMBAK KOTA PEKALONGAN - Evida Amalia; Hayati Soeprapto; M Bahrus Syakirin (Fakultas Perikanan Universitas Pekalongan, 2017)
Tilapia fish (Oreochromis niloticus) is one of freshwater commodities gained big attentionfrom governments abd obsevers of world fisheries issues, especially related to raising nutritients in countries – developing countries. The succes of Tilapias related to environment healthy and fish disease caused by bacteria. One of bacteria found in aquatic ecosystems is Escherichia coli. This research has a purpose to know there are Escherichia coli at Tilapia fish cultivation and to know the existence of contamination from cultivation media. This research is done on February 24th until March 6th, 2015. The research used sample purposive sampling, sample was taken at three fishpond locations, there was slamaran and Degayu. Then, sample was analyzed at Laboratory testing and Quality Control of Fishery Product ( LPPMHP), Pekalongan City. The research result show that Escherichia coli content in first fishpond is 3,6 MPN/gr, second fishpond is 9,4 MPN/gr and the last fishpond is 9,3 MPN/gr. Another side, Escherichia coli content of meat Tilapias is less than 3 MPN/gr for each cultivation, either in Slamaran or Degayu. It is stated that the content of E.coli in the pond water does not contaminate tilapia fish. Tilapia fish is safe for consumption. Keywords : Escherichia coli, fishpond, tilapia fish